CONVERGENCE THEOREMS FOR OPERATORS WITH PROPERTY (E) IN CAT(0) SPACES - Temir, S. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2024)
In this paper, we study the convergence of the SP*-iteration process to fixed point for operators with property (E) in CAT(0) spaces. We also prove the stability of the SP*-iteration process in CAT(0) spaces. Our results improve and extend some recently results in the literature of fixed point theory in CAT(0) spaces.